2014
DOI: 10.1039/c4nr03301a
|View full text |Cite
|
Sign up to set email alerts
|

Gel-limited synthesis of dumbbell-like Fe3O4–Ag composite microspheres and their SERS applications

Abstract: A novel gel-limited strategy was developed to synthesize dumbbell-like Fe3O4-Ag composite microspheres through a simple one-pot solvothermal method. In such a reaction system, a special precursor solution containing oleic, water, ethanol and silver ions was used and transformed into a bulk gel under heating at the very beginning of the reaction, thus all the subsequent reactions proceeded in the interior of the gel. The gel-limited reactions had two advantages, on the one hand, the magnetic Fe3O4 microspheres … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…From the TEM images of FePt–Ag 5 mg–60 mL and FePt–Ag 10 mg–60 mL, Ag seeds are found to be coherent with FePt nanocrystals owing to the effect of the two chelating sulfur groups provided by the PEI-DTC polymers. It is commonly known that the brightness in the TEM image reflects the ability of the transmitted electrons from the different substances and is proportional to the atomic number of the substances [ 62 ]. Unfortunately, because both FePt and Ag nanocrystals have high atomic numbers, it is hard to distinguish the two nanomaterials from TEM images.…”
Section: Resultsmentioning
confidence: 99%
“…From the TEM images of FePt–Ag 5 mg–60 mL and FePt–Ag 10 mg–60 mL, Ag seeds are found to be coherent with FePt nanocrystals owing to the effect of the two chelating sulfur groups provided by the PEI-DTC polymers. It is commonly known that the brightness in the TEM image reflects the ability of the transmitted electrons from the different substances and is proportional to the atomic number of the substances [ 62 ]. Unfortunately, because both FePt and Ag nanocrystals have high atomic numbers, it is hard to distinguish the two nanomaterials from TEM images.…”
Section: Resultsmentioning
confidence: 99%
“…Several attempts have been taken to design new hybrid nanocomplexes with well-defined multicomponents by controlling the size and shapes of these materials through solution growth structure [89][90][91]. Nasrollahjadeh et al [4] reported on the eco-friendly synthesis of Pd/Fe 3 O 4 NPs using Euphorbia condylocarapa M. bieb root extract and applied as a magnetically recyclable catalyst for Suzuki and Sonogashira coupling reaction.…”
Section: Flower-like Pd-fe 3 O 4 and Pd-fe 3 O 4 Hybrid Nanocatalyst-mentioning
confidence: 99%
“…As illustrated in Scheme 1a, the target analyte with specic affinity could be enriched with SiO 2 @PEI@Ag NPs; the formed complexes were separated by centrifugation and dropped on a silicon chip for SERS measurement. We detected the Raman signals of trace thiram, a widely used sulfur-containing fungicide, 37,38 to prove the practicability of the SiO 2 @PEI@Ag NPs. The Raman mapping of the thiram at the 1383 cm À1 band conrms the good reproducibility and reliability of Raman detection with SiO 2 @PEI@Ag NPs as SERS substrate (Fig.…”
Section: Rsc Advances Papermentioning
confidence: 99%